2020
DOI: 10.3892/mmr.2020.11009
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA MALAT1 promotes high glucose‑induced rat cartilage endplate cell apoptosis via the p38/MAPK signalling pathway

Abstract: diabetes mellitus (dM) contributes to intervertebral disc degeneration (idd). The long non-coding rna MalaT1 has been revealed to play an important role in diabetes-associated complications. However, the specific role of MALAT1 in diabetes-associated idd has not been determined. The aim of the present study was to evaluate the roles of MALAT1 in the apoptosis of cartilage endplate (CEP) cells induced by high glucose and to explore the mechanisms underlying this effect. rat ceP cells were cultured in high-gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…We identified 9511 published studies related to the issue IVDD. Out of these 27 manuscripts were related to the topic IVDD in diabetic rodent models, which is our research field of interest [ 3 , 15 , 43 , 47 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ], see Table 4 and Table 5 . By further evaluation another four publications were excluded; two of them discussed the diabetic animal models used in IVDD, including rodents, but they were not related to IVDD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 9511 published studies related to the issue IVDD. Out of these 27 manuscripts were related to the topic IVDD in diabetic rodent models, which is our research field of interest [ 3 , 15 , 43 , 47 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ], see Table 4 and Table 5 . By further evaluation another four publications were excluded; two of them discussed the diabetic animal models used in IVDD, including rodents, but they were not related to IVDD.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies, investigated the overall pathogenesis of DM in the development of IVDD, see Table 4 , [ 53 , 54 , 55 , 56 , 57 , 59 , 61 , 63 , 64 , 65 , 67 , 69 ], while two studies investigated a specific pathogenesis element [ 58 , 66 ], such as the role of Sirt1/p53 axis in diabetic IVDD and the effect of metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) on apoptosis promoted by high glucose in rat cartilage endplate (CEP) cells. The other four studies (17.4%) investigated the effect and pathogenesis of risk factors [ 3 , 52 , 60 , 70 ], such as the degenerative effect on spine/IVD tissues induced by chronic ingestion of AGEs and the long exposure to high glucose concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mounting studies have suggested the correlations of lncRNAs with diabetic complications. For instance, MALAT1 enhanced the HG-induced cartilage endplate cell apoptosis by the p38/MAPK signaling pathway [ 30 ] and CASC15 promoted diabetes-induced chronic renal failure and podocyte apoptosis [ 31 ]. It has been found that MIAT facilitated diabetic retinopathy via activating TGF-β1 signaling [ 32 ] and induced cardiomyocyte apoptosis in diabetic cardiomyopathy by targeting the miR-22-3p/DAPK2 axis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%